Etos Kerja Islam Sebagai Upaya Meningkatkan Kinerja Organisasi - Nanda Hidayan Sono (Program Pascasarjana Universitas Ibrahimy, 2017)
This article illustrates the role of Islamic Work Ethic. The Working Ethos of Islam is a personality attitude gives rise to a profound belief that work isn’t only to glorify itself, but also as a manifestation of righteous deeds, therefore has a very high value of worship. Successful organizations seem to have a strong Islamic work ethic. It can improve performance. This article has several aspects of the work ethic are studied and analyzed by bringing theory into real conditions, there by impacting the worker's performance then illustrates the role of Islamic Work Ethic. The Working Ethos of Islam is a personality attitude gives rise to a profound belief, the work isn’t only to glorify itself, to reveal humanity, but also as a manifestation of righteous deeds, therefore to have a very noble value of worship. Successful organizations seem to have a strong Islamic work ethic can improve performance. This article, several aspects of the work ethic are studied and analyzed by bringing together theories with real conditions, affect the performance of workers.